2022
DOI: 10.1007/s00467-022-05813-w
|View full text |Cite
|
Sign up to set email alerts
|

Humoral and cellular immune response to SARS-CoV-2 mRNA BNT162b2 vaccine in pediatric kidney transplant recipients compared with dialysis patients and healthy children

Abstract: Background Compared with the general population, the immune response to COVID-19 mRNA vaccines is lower in adult kidney transplant recipients (KTRs). However, data is limited for pediatric KTRs. In this study, we aimed to assess humoral and cellular immune responses to the COVID-19 mRNA vaccine in pediatric KTRs. Methods This multicenter, prospective, case-control study included 63 KTRs (37 male, aged 12-21 years), 19 dialysis patients, and 19 controls. Humoral (anti-SARS-CoV2 IgG, neutralizing Ab (nAb)) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…Unlike for the adult transplant population 45,54–56 adding a third dose for the pediatric kidney transplant recipients may not be necessary to improve seroconversion rates (i.e., S antibody titer). Despite the limitation of the small sample size, it is noteworthy that the seroconversion after a two‐dose series was significantly better in younger age groups than that in the adult population, supporting the argument that pediatric SOT recipients can mount a more robust measured antibody response to vaccination than adult patients, as is consistent with prior reports 21,42,57,58 …”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Unlike for the adult transplant population 45,54–56 adding a third dose for the pediatric kidney transplant recipients may not be necessary to improve seroconversion rates (i.e., S antibody titer). Despite the limitation of the small sample size, it is noteworthy that the seroconversion after a two‐dose series was significantly better in younger age groups than that in the adult population, supporting the argument that pediatric SOT recipients can mount a more robust measured antibody response to vaccination than adult patients, as is consistent with prior reports 21,42,57,58 …”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have shown that children who received the Pfizer vaccine are less likely to have severe COVID‐19 18–23 . Like adults, children can also have adverse reactions from the COVID‐19 vaccines, including sore arms, muscle aches, fever, and chills.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations